Critical organic modifier aliphatic tail length for the formation of poly(methyl methacrylate)-montmorillonite nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2020)
In this article, we report the influence of organic modifier structure (alkyl chain length C8-C20, single vs ditallow) and thereby, the effect of hydrophobicity on the structure, thermal and mechanical properties of poly(methyl methacrylate) (PMMA)-clay hybrids. Melt processed PMMA-clay hybrids were characterized using wide-angle X-ray diffraction, transmission electron microscopy, and differential scanning calorimetry. The organoclays having an alkyl chain length of more than 12 CH2 groups resulted in the formation of nanocomposites. The glass transition temperature (T-g) of PMMA increased in the presence of clay. The mean-field lattice model was used to predict the free energy for nanocomposite formation, which showed a reasonable match with the experimental results and provided a general guideline for the proper selection of polymer and organoclay (ie, organic modifier) to obtain nanocomposite. Tensile modulus showed maximum improvement of 58% for the nanocomposites compared to 9% improvement for the composites. Tensile modulus increased with increases in the alkyl chain length of the organic modifier and clay loading. The level of improvement for the tensile properties of nanocomposites prepared from primary and secondary ammonium-modified clay is the same as that obtained with the commercial organoclays.
Keywords: hybrid; mechanical properties; Montmorillonite; Nanocomposites; organoclay; poly(methyl methacrylate)